Prevalenca protiteles proti bakteriji Helicobacter pylori v Sloveniji v letu 2005 - Gubina, Marija (Zdravniški vestnik, 2006)
Background Helicobacter pylori infection is the most common human infection. Its prevalence is declin- ing in the Western world because of better sanitation and living conditions and because of medical treatment of symptomatic carriers of infection. The aim of the study was to find out the prevalence of infection in Slovenia in 2005. The antibody titer against bacteria Helicobacter pylori in tested sera was applied as detection tool. Patients and Serum samples from 1045 individuals from 0 to 90 years of age were collected. The labora- tory investigations by ELISA tests for IgG and IgAantibodies to Helicobacter pylori were performed at the Institute of Microbiology and Immunology Medical Faculty in Ljubljana. Patients were divided by decades into age groups, and by sex into male and female groups. Results The prevalence of seropositivity increases with age; there is no difference between men and women. The mean seropositivity rate is 25.1 % (95% CI 23-28%). The peak seropositi- vity rate is 54% (95% CI 40-69%) in the age group 60 to 69 years. There are 9.4% positive participants in the age group 0 to 19 and 29.6% seropositive participants in the age group between 20 and 49 years. Conclusions The Helicobacter pylori seropositivity rate has fallen dramatically in the last 15 years. The re is still more than one quarter of population younger than 45 years infected, which is very important in decidingabout the right therapeutic approach to that particular segment of ourpopulation.
Keywords: Age Factors; Antibodies, Bacterial; bakterijske okužbe; Epidemiology; Helicobacter Infections; Helicobacter Pylori; Helicobacter, infekcije; IgA; IgG; Immunology; prevalenca; protitelesa; Protitelesa bakterijska; Sex Factors; Spolni faktorji; Starostni faktorji